Some New Results on Vibrational Properties of Amorphous Group IV Semiconductors - M. A. Grado Caffaro; M. Grado Caffaro (Active and Passive Electronic Components)
For neutron scattering, an interesting formula is derived from the coherent one-phonon dynamic structure factor. In this derivation, phonon density of states is involved; this density is related to spectra due to structural disorder, which is investigated. Our considerations refer to amorphous Group IV semiconductors.